2022
DOI: 10.1039/d1ra07390g
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the 1,3-azadiene-anhydride reaction for the synthesis of functionalized piperidines bearing up to five contiguous stereocenters

Abstract: A modular and scalable strategy, which converts 3-methylglutaric anhydride to 2-oxopiperidines bearing at least three contiguous stereocenters is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…In the last decade, we have sought to popularize the 1,3-azadiene-anhydride reaction for the stereocontrolled synthesis of lactam-bearing 5-aryl-4( E )-pentenoic acids of type 1 (ref. 10 ) ( Fig. 2A ) and subsequent post-diversification.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, we have sought to popularize the 1,3-azadiene-anhydride reaction for the stereocontrolled synthesis of lactam-bearing 5-aryl-4( E )-pentenoic acids of type 1 (ref. 10 ) ( Fig. 2A ) and subsequent post-diversification.…”
Section: Introductionmentioning
confidence: 99%
“…, glutaric anhydride, 2,2-dimethylglutaric anhydride, 3-methylglutaric anhydride, diglycolic anhydride, thiodiglycolic anhydride, and MIDA anhydride) react competently with appropriately substituted 1,3-azadienes. 9 a – g Recently, we revealed that highly reactive phenylsuccinic anhydride is amenable to chemoselective and stereocontrolled pentannulation with 1,3-azadienes at room temperature. 9 h – j…”
Section: Introductionmentioning
confidence: 99%
“…Fragment libraries consisting of a variety of 3D scaffolds are expected to display a wider range of biological activities compared to single scaffold libraries. Within this context, and as part of a program aimed at leveraging the synthetic versatility of the 1,3-azadiene-anhydride reaction, 8 our group has identified the catalytic halolactonization 8 g , h of lactam-bearing alkenoic acids of type 1 ( Fig. 2A/B ) and subsequent interrogation of the lactam-halolactones (see 2/3) in fragment growth protocols as an important research objective ( Fig.…”
Section: Introductionmentioning
confidence: 99%